The dimensions of deliberation in the book of the best formulation in the Halia of rhetoric - ألسخاذ امىساعد امدكخِر دمخِش جاراهلل حسٔي دزه ْٓ; د.وُاةاد َاشه إةرأَه (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The present study is a new pragmatic reading of Arabic rhetoric represented by Alwa’idh’s book ‘Ahsan Alsiyaghah fi HilyatAlbalaghah’. The study reflects the Kurdish scholars’ role in developing the Islamic and rhetoric heritage. It also shows those scholars’ views in this field as a way of contributing to a better understanding of the miraculous aspects of the Holy Koran. Alwa’idh’s views and analyses were not repetition of his predecessors’; his classification, explanation, and analyses were his own. His style is characterized by simplicity and intensity. Moreover, he follows a scientific methodology which shows his acquaintance with the different branches of rhetoric. The pragmatic aspects that were highlighted in his book were limited to such concepts as intentionality, conversational implicature, presupposition, and speech acts. It is worth mentioning that Alwa’idh used some terms that are at the heart of pragmatics in the course of his analyses.